A method for preparing antibacterial and highly wear-resistant BOPP printed film

By using the electro-adsorption of silicon oxygen system and chitosan on the BOPP film, the poor wear resistance and bacterial growth problems of BOPP film are solved, and the preparation of antibacterial high wear resistance BOPP printing film is realized.

CN118514403BActive Publication Date: 2025-04-18ZHEJIANG KINCESS INNOVATIVE MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410639154.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2025-04-18
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

The existing BOPP film has poor wear resistance and is prone to damage, and is prone to bacterial growth during transportation and processing, affecting the packaging quality.

Method used

The silicon oxygen system is used to form a wear-resistant structure and bacterial repulsion surface layer, and an antibacterial and antibacterial system is formed by combining the electro-adsorption of chitosan to form an antibacterial and antibacterial system to prepare an antibacterial high wear-resistant BOPP printing film.

Benefits of technology

It realizes the balance of antibacterial and wear resistance of BOPP films, and improves its protective performance and stability during transportation and processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004852784330000091
    Figure BDA0004852784330000091
Patent Text Reader

Abstract

The present invention belongs to the technical field of BOPP films, and specifically relates to a method for preparing an antibacterial and highly wear-resistant BOPP printed film, wherein the BOPP printed film comprises a polypropylene base layer and a wear-resistant layer coated on the surface of the polypropylene base layer, wherein the thickness of the polypropylene base layer is 20-40 μm, the thickness of the wear-resistant layer is 30-50 μm, the wear-resistant layer has an antibacterial effect, and provides a formula and a preparation method of the BOPP printed film. The present invention solves the defects of the existing BOPP film, utilizes a silicon-oxygen system to form a wear-resistant structure and a bacteria-repelling surface layer, and cooperates with the electrical adsorption of chitosan to form an antibacterial and antibacterial system, thereby achieving both antibacterial and wear-resistant properties of the BOPP film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of BOPP films, and in particular relates to a method for preparing an antibacterial and highly wear-resistant BOPP printed film. Background Art

[0002] BOPP film, also known as biaxially oriented polypropylene film, is a very important flexible packaging material. It is colorless, odorless, non-toxic, and has good overall performance. However, during transportation and processing, products often need to be covered with BOPP film for protection. However, the current BOPP film has many disadvantages, such as poor wear resistance and easy damage. At the same time, bacteria are prone to breeding in the transportation and processing environment, and even accumulate on the BOPP film used as packaging. Therefore, the market needs a packaging material that is both wear-resistant and antibacterial. Summary of the invention

[0003] In view of the problems in the prior art, the present invention provides a method for preparing an antibacterial and highly wear-resistant BOPP printed film, which solves the defects of the existing BOPP film, utilizes the silicon-oxygen system to form a wear-resistant structure and a bacteria-repelling surface layer, and cooperates with the electrical adsorption of chitosan to form an antibacterial and antibacterial system, thereby achieving both antibacterial and wear-resistant properties of the BOPP film.

[0004] In order to achieve the above technical objectives, the technical solution of the present invention is:

[0005] A method for preparing an antibacterial and highly wear-resistant BOPP printed film. The BOPP printed film comprises a polypropylene base layer and a wear-resistant layer coated on the surface of the polypropylene base layer. The thickness of the polypropylene base layer is 20-40 μm, the thickness of the wear-resistant layer is 30-50 μm, and the wear-resistant layer has an antibacterial effect.

[0006] The mass ratio of the polypropylene base layer is: 70-80 parts of polypropylene resin, 3-6 parts of silane coupling agent, and 0.1-0.5 parts of antistatic agent; the polypropylene resin adopts homopolymer polypropylene with the brand F280F produced in Shaoxing and a melt index of 2.8g / 10min (230°C, 2.16kg); the silane coupling agent adopts; the antistatic agent adopts ethoxylated alkyl acid amine.

[0007] The mass ratio of the wear-resistant layer is: 50-70 parts of polypropylene resin, 30-50 parts of wear-resistant agent, 1-3 parts of antioxidant, 0.4-0.6 parts of dispersant, and 2-4 parts of stabilizer.

[0008] The polypropylene resin is homopolymer polypropylene with a brand name of F280F, produced in Shaoxing, and a melt index of 2.8 g / 10 min (230° C., 2.16 kg).

[0009] The wear-resistant agent adopts a chitosan-silicon composite wear-resistant agent, which has chitosan as a core and a silicon material as a porous protective shell, and there is a gap between the core and the porous protective shell. During use, the silicon material on the surface of the wear-resistant agent itself has a relatively stable structure and mechanical strength, and exhibits certain ceramic properties after being solidified in a polypropylene resin; the silicon material belongs to a silica-based material, and has a certain negative charge on the surface, which can have a good negative charge repulsion to dust and ensure the cleanliness of the surface. At the same time, the amino glucosamine molecules in the structure of chitosan itself have a positive charge, which communicates with the negative charge on the surface of the bacteria, thereby achieving the effect of inactivating the bacteria, that is, chitosan can not only gather bacteria in the form of electrical adsorption, but also use its own bactericidal properties to achieve bactericidal and antibacterial properties of the wear-resistant layer, thereby reducing the impact of bacteria on the printed film. There is a certain gap between the chitosan core and the silicone shell, and the gap can effectively reduce the direct attraction between chitosan and silicone materials, ensuring that a certain degree of active groups of chitosan are exposed; therefore, the chitosan-silicone composite wear-resistant agent has both wear resistance and antibacterial properties. The preparation method of the chitosan-silicone composite wear-resistant agent comprises the following steps: a1, dispersing chitosan in ethanol to form a suspension, then adding polyvinyl pyrrolidone for ultrasonic treatment for 10-30 minutes, filtering and drying to obtain polyvinyl pyrrolidone-coated chitosan; the mass ratio of chitosan to ethanol is 1:5-7, the dispersion treatment adopts mechanical stirring treatment, the stirring speed is 1000-2000r / min, the mass ratio of polyvinyl pyrrolidone to chitosan is 1:2-3, the ultrasonic frequency of ultrasonic treatment is 70-90kHz, and the ultrasonic temperature is 20-30℃; the drying temperature is 80-90℃; this step utilizes the insolubility of chitosan in ethanol a2, adding trichlorophenylsilane and ethyl cellulose to ether and stirring evenly, then adding polyvinyl pyrrolidone to wrap chitosan and stirring for 10-20min, after suction filtration and drying, obtaining coated chitosan, wherein the mass ratio of trichlorophenylsilane to ethyl cellulose is 6-8:1, the concentration of ethyl cellulose in ether is 30-70g / L, the stirring speed for even stirring is 1000-2000r / min, and the mass ratio of polyvinyl pyrrolidone to wrap chitosan and trichlorophenylsilane is 1:1.2-1.5, the stirring speed is 100-200r / min, and the drying temperature is 40-50°C; this step utilizes the solubility of trichlorophenylsilane and ethyl cellulose in ether and the insolubility of polyvinyl pyrrolidone in ether, and distributes the ether liquid on the surface of polyvinyl pyrrolidone during the soaking process to form a liquid film containing trichlorophenylsilane; a3, the coated chitosan is allowed to stand for 1-2h, and the temperature is increased for 0.5-1h to obtain a prefabricated wear-resistant agent, the atmosphere of the standing is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8-10:1; the temperature of the temperature increase treatment is 120-140°C; this step uses the coated chitosan obtained in the previous step, and it is allowed to stand in an atmosphere containing water vapor, and water molecules and trichlorophenylsilane form hydrolysis to obtain trihydroxyphenylsilane, and the reaction is located at The surface of the coated particles, and ethyl cellulose is insoluble in water, therefore, the amount of water molecules penetrating into polyvinyl pyrrolidone is very small, the effect is extremely small and can be ignored, and trihydroxyphenylsilane forms hydroxyl condensation during the heating process, thereby forming a phenylsiloxane structure; a4, placing the prefabricated wear-resistant agent into ethanol for ultrasonic treatment for 1-3h, filtering and washing with ethanol and drying to obtain the wear-resistant agent, the concentration of the prefabricated wear-resistant agent in ethanol is 200-500g / L, the ultrasonic frequency of the ultrasonic treatment is 90-100kHz, and the temperature is 40-50℃; the drying temperature is 100-110℃; this step utilizes the solubility of ethyl cellulose and polyvinyl pyrrolidone in ethanol, and dissolves the ethyl cellulose and polyvinyl pyrrolidone in the prefabricated wear-resistant agent in ultrasound to form a porous silicon structure and a chitosan core. The wear-resistant agent prepared by this process utilizes the solubility and insolubility of ethyl cellulose and polyvinyl pyrrolidone to form layers of coatings, and after the reaction is stable, the solubility of ethanol is utilized to dissolve and recycle the ethyl cellulose and polyvinyl pyrrolidone.

[0010] The antioxidant is antioxidant 1010 or antioxidant 168.

[0011] The dispersant is zinc stearate.

[0012] The stabilizer adopts calcium zinc composite stabilizer.

[0013] The method for preparing the antibacterial high wear-resistant BOPP printed film comprises the following steps:

[0014] Step 1, drying the polypropylene resin, silane coupling agent and antistatic agent respectively, adding them to an extruder and mixing them evenly, and melt-extrude them to obtain a matrix melt; the temperature of the melt extrusion is 240-250° C.;

[0015] Step 2, adding polypropylene resin, anti-wear agent, antioxidant, dispersant and stabilizer to the extruder, mixing evenly, and melt-extrude to obtain a wear-resistant melt; the temperature of the melt extrusion is 230-240°C;

[0016] Step 3, the base melt and the wear-resistant melt are extruded in the order of the die lip of the double-layer structure extruder to obtain a film, and then rapidly cooled to obtain a cast sheet;

[0017] Step 4, stretching the cast sheet longitudinally at a constant temperature, and then stretching it transversely at a constant temperature, and cooling it to obtain an antibacterial and highly wear-resistant BOPP film, wherein the preheating temperature of the longitudinal stretching is 140-150°C, the stretching temperature is 130-140°C, and the stretching ratio is 4-6 times; the preheating temperature of the transverse stretching is 165-175°C, the stretching temperature is 160-170°C, and the stretching ratio is 7-9 times, and the cooling is natural cooling and rapid cooling to fix the shape.

[0018] It can be seen from the above description that the present invention has the following advantages:

[0019] 1. The present invention solves the defects of the existing BOPP film, uses the silicon-oxygen system to form a wear-resistant structure and a bacteria-repelling surface layer, and cooperates with the electrical adsorption of chitosan to form an antibacterial and antibacterial system, thereby achieving both antibacterial and wear-resistant properties of the BOPP film.

[0020] 2. The present invention uses trichlorophenylsilane as a raw material to form a phenyl-silicon oxygen system, and combines zinc stearate and calcium-zinc composite stabilizers to form an excellent heat-resistant flame-retardant system, showing excellent heat resistance.

[0021] 3. The present invention utilizes the low content of ethyl cellulose in trichlorophenylsilane to form a small pore structure of the phenylsiloxane shell layer, which provides good protection during the extrusion process. At the same time, the polypropylene resin is used as a curing resin and can be connected with the polypropylene base layer to form an integrated structure. DETAILED DESCRIPTION

[0022] The present invention is described in detail with reference to the embodiments, but no limitation is imposed on the claims of the present invention.

[0023] Example 1

[0024] A method for preparing antibacterial and highly wear-resistant BOPP printed film

[0025] The BOPP printing film comprises a polypropylene base layer and a wear-resistant layer coated on the surface of the polypropylene base layer:

[0026] The mass ratio of the polypropylene base layer is: 70 parts of polypropylene resin, 3 parts of silane coupling agent, and 0.1 parts of antistatic agent; the polypropylene resin adopts homopolymer polypropylene with the brand name F280F, produced in Shaoxing, and the melt index is 2.8g / 10min (230°C, 2.16kg), the silane coupling agent adopts; the antistatic agent adopts ethoxylated alkyl acid amine.

[0027] The mass ratio of the wear-resistant layer is: 50 parts of polypropylene resin, 30 parts of wear-resistant agent, 1 part of antioxidant, 0.4 parts of dispersant and 2 parts of stabilizer.

[0028] The polypropylene resin is homopolymer polypropylene with a brand name of F280F, produced in Shaoxing, and a melt index of 2.8 g / 10 min (230° C., 2.16 kg).

[0029] The wear-resistant agent adopts a chitosan-silicone composite wear-resistant agent, wherein the chitosan-silicone composite wear-resistant agent has chitosan as a core and a silicon material as a porous protective shell, and there is a gap between the core and the porous protective shell. The preparation method of the chitosan-silicone composite wear-resistant agent comprises the following steps: a1, dispersing chitosan in ethanol to form a suspension, then adding polyvinyl pyrrolidone and ultrasonically treating it for 10 minutes, filtering and drying to obtain polyvinyl pyrrolidone-coated chitosan; the mass ratio of chitosan to ethanol is 1:5, the dispersion treatment adopts mechanical stirring treatment, the stirring speed is 1000r / min, the mass ratio of polyvinyl pyrrolidone to chitosan is 1:2, the ultrasonic frequency of the ultrasonic treatment is 70kHz, and the ultrasonic temperature is 20°C; the drying temperature is 80°C; a2, adding trichlorophenylsilane and ethyl cellulose to ether and stirring evenly, then adding polyvinyl pyrrolidone to wrap chitosan and stirring for 10 minutes, filtering and drying and drying to obtain coated chitosan, the mass ratio of trichlorophenylsilane to ethyl cellulose is 6:1, the concentration of ethyl cellulose in ether is 30g / L, the stirring speed for uniform stirring is 1000r / min, the mass ratio of polyvinyl pyrrolidone-wrapped chitosan to trichlorophenylsilane is 1:1.2, the stirring speed is 100r / min, and the drying temperature is 40°C; a3, the coated chitosan is allowed to stand for 1-2h, and the temperature is increased for 0.5h to obtain a prefabricated wear-resistant agent, the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1; the temperature of the heating treatment is 120°C; a4, the prefabricated wear-resistant agent is placed in ethanol for ultrasonic treatment for 1-3h, filtered, washed with ethanol and dried to obtain a wear-resistant agent, the concentration of the prefabricated wear-resistant agent in ethanol is 200g / L, the ultrasonic frequency of the ultrasonic treatment is 90kHz, and the temperature is 40°C; the drying temperature is 100°C.

[0030] The antioxidant used is antioxidant 1010 8.

[0031] The dispersant is zinc stearate.

[0032] The stabilizer adopts calcium zinc composite stabilizer.

[0033] The thickness of the BOPP printing film is 50 μm, wherein the thickness of the polypropylene base layer is 20 μm, and the thickness of the grinding layer is 30 μm.

[0034] The method for preparing the antibacterial high wear-resistant BOPP printed film comprises the following steps:

[0035] Step 1, drying the polypropylene resin, silane coupling agent and antistatic agent respectively, adding them to an extruder and mixing them evenly, and melt-extrude them to obtain a matrix melt; the temperature of the melt extrusion is 240-250° C.;

[0036] Step 2, adding polypropylene resin, anti-wear agent, antioxidant, dispersant and stabilizer to the extruder, mixing evenly, and melt-extrude to obtain a wear-resistant melt; the temperature of the melt extrusion is 230-240°C;

[0037] Step 3, the base melt and the wear-resistant melt are extruded in the order of the die lip of the double-layer structure extruder to obtain a film, and then rapidly cooled to obtain a cast sheet;

[0038] Step 4, stretching the cast sheet longitudinally at a constant temperature, and then stretching it transversely at a constant temperature, and cooling it to obtain an antibacterial and highly wear-resistant BOPP film, wherein the preheating temperature of the longitudinal stretching is 140°C, the stretching temperature is 130°C, and the stretching ratio is 6 times; the preheating temperature of the transverse stretching is 165°C, the stretching temperature is 160°C, and the stretching ratio is 9 times, and the cooling is natural cooling and rapid cooling to fix the shape.

[0039] Example 2

[0040] A method for preparing antibacterial and highly wear-resistant BOPP printed film

[0041] The BOPP printing film comprises a polypropylene base layer and a wear-resistant layer coated on the surface of the polypropylene base layer:

[0042] The mass ratio of the polypropylene base layer is: 80 parts of polypropylene resin, 6 parts of silane coupling agent, and 0.5 parts of antistatic agent; the polypropylene resin adopts homopolymer polypropylene, the brand is F280F, the place of origin is Shaoxing, the melt index is 2.8g / 10min (230°C, 2.16kg), the silane coupling agent adopts; the antistatic agent adopts ethoxylated alkyl acid amine.

[0043] The mass ratio of the wear-resistant layer is: 70 parts of polypropylene resin, 50 parts of wear-resistant agent, 3 parts of antioxidant, 0.6 parts of dispersant and 4 parts of stabilizer.

[0044] The polypropylene resin is homopolymer polypropylene with a brand name of F280F, produced in Shaoxing, and a melt index of 2.8 g / 10 min (230° C., 2.16 kg).

[0045] The wear-resistant agent adopts a chitosan-silicone composite wear-resistant agent, wherein the chitosan-silicone composite wear-resistant agent has chitosan as a core and a silicon material as a porous protective shell, and there is a gap between the core and the porous protective shell. The preparation method of the chitosan-silicone composite wear-resistant agent comprises the following steps: a1, dispersing chitosan in ethanol to form a suspension, then adding polyvinyl pyrrolidone and ultrasonically treating it for 30 minutes, filtering and drying to obtain polyvinyl pyrrolidone-coated chitosan; the mass ratio of chitosan to ethanol is 1:7, the dispersion treatment adopts mechanical stirring treatment, the stirring speed is 2000r / min, the mass ratio of polyvinyl pyrrolidone to chitosan is 1:3, the ultrasonic frequency of the ultrasonic treatment is 90kHz, and the ultrasonic temperature is 30°C; the drying temperature is 90°C; a2, adding trichlorophenylsilane and ethyl cellulose to ether and stirring evenly, then adding polyvinyl pyrrolidone to wrap chitosan and stirring for 20 minutes, filtering and drying After filtration and drying, a coated chitosan is obtained, the mass ratio of trichlorophenylsilane and ethyl cellulose is 8:1, the concentration of ethyl cellulose in ether is 70g / L, the stirring speed for uniform stirring is 2000r / min, the mass ratio of polyvinyl pyrrolidone-coated chitosan and trichlorophenylsilane is 1:1.5, the stirring speed is 200r / min, and the drying temperature is 50°C; a3, the coated chitosan is allowed to stand for 2h, and the temperature is increased for 1h to obtain a prefabricated wear-resistant agent, the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10:1; the temperature of the heating treatment is 140°C; a4, the prefabricated wear-resistant agent is placed in ethanol for ultrasonic treatment for 3h, filtered, washed with ethanol and dried to obtain a wear-resistant agent, the concentration of the prefabricated wear-resistant agent in ethanol is 500g / L, the ultrasonic frequency of the ultrasonic treatment is 100kHz, and the temperature is 50°C; the drying temperature is 110°C.

[0046] The antioxidant used is antioxidant 168.

[0047] The dispersant is zinc stearate.

[0048] The stabilizer adopts calcium zinc composite stabilizer.

[0049] The thickness of the BOPP printing film is 90 μm, wherein the thickness of the polypropylene base layer is 40 μm, and the thickness of the wear-resistant layer is 50 μm.

[0050] The method for preparing the antibacterial high wear-resistant BOPP printed film comprises the following steps:

[0051] Step 1, drying the polypropylene resin, silane coupling agent and antistatic agent respectively, adding them to an extruder and mixing them evenly, and melt-extrude them to obtain a matrix melt; the temperature of the melt extrusion is 240-250° C.;

[0052] Step 2, adding polypropylene resin, anti-wear agent, antioxidant, dispersant and stabilizer to the extruder, mixing evenly, and melt-extrude to obtain a wear-resistant melt; the temperature of the melt extrusion is 230-240°C;

[0053] Step 3, the base melt and the wear-resistant melt are extruded in the order of the die lip of the double-layer structure extruder to obtain a film, and then rapidly cooled to obtain a cast sheet;

[0054] Step 4, stretching the cast sheet longitudinally at a constant temperature, and then stretching it transversely at a constant temperature, and cooling it to obtain an antibacterial and highly wear-resistant BOPP film, wherein the preheating temperature of the longitudinal stretching is 150°C, the stretching temperature is 140°C, and the stretching ratio is 4 times; the preheating temperature of the transverse stretching is 175°C, the stretching temperature is 170°C, and the stretching ratio is 7 times, and the cooling is natural cooling and rapid cooling to fix the shape.

[0055] Example 3

[0056] A method for preparing antibacterial and highly wear-resistant BOPP printed film

[0057] The BOPP printing film comprises a polypropylene base layer and a wear-resistant layer coated on the surface of the polypropylene base layer:

[0058] The mass ratio of the polypropylene base layer is: 75 parts of polypropylene resin, 5 parts of silane coupling agent, and 0.3 parts of antistatic agent; the polypropylene resin adopts homopolymer polypropylene, the brand is F280F, the place of origin is Shaoxing, the melt index is 2.8g / 10min (230°C, 2.16kg), the silane coupling agent adopts; the antistatic agent adopts ethoxylated alkyl acid amine.

[0059] The mass ratio of the wear-resistant layer is: 60 parts of polypropylene resin, 40 parts of wear-resistant agent, 2 parts of antioxidant, 0.5 parts of dispersant and 3 parts of stabilizer.

[0060] The polypropylene resin is homopolymer polypropylene with a brand name of F280F, produced in Shaoxing, and a melt index of 2.8 g / 10 min (230° C., 2.16 kg).

[0061] The wear-resistant agent adopts a chitosan-silicone composite wear-resistant agent, wherein the chitosan-silicone composite wear-resistant agent has chitosan as a core and a silicon material as a porous protective shell, and there is a gap between the core and the porous protective shell. The preparation method of the chitosan-silicone composite wear-resistant agent comprises the following steps: a1, dispersing chitosan in ethanol to form a suspension, then adding polyvinyl pyrrolidone and ultrasonically treating it for 20 minutes, filtering and drying to obtain polyvinyl pyrrolidone-coated chitosan; the mass ratio of chitosan to ethanol is 1:6, the dispersion treatment adopts mechanical stirring treatment, the stirring speed is 1500r / min, the mass ratio of polyvinyl pyrrolidone to chitosan is 1:3, the ultrasonic frequency of the ultrasonic treatment is 80kHz, and the ultrasonic temperature is 25°C; the drying temperature is 85°C; a2, adding trichlorophenylsilane and ethyl cellulose to ether and stirring evenly, then adding polyvinyl pyrrolidone to wrap chitosan and stirring for 15 minutes, After filtration and drying, the coated chitosan is obtained, the mass ratio of trichlorophenylsilane and ethyl cellulose is 7:1, the concentration of ethyl cellulose in ether is 60g / L, the stirring speed for uniform stirring is 1500r / min, the mass ratio of polyvinyl pyrrolidone-coated chitosan and trichlorophenylsilane is 1:1.4, the stirring speed is 150r / min, and the drying temperature is 45°C; a3, the coated chitosan is allowed to stand for 2h, and the temperature is increased for 1h to obtain a prefabricated wear-resistant agent, the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 9:1; the temperature of the heating treatment is 130°C; a4, the prefabricated wear-resistant agent is placed in ethanol for ultrasonic treatment for 2h, filtered, washed with ethanol and dried to obtain a wear-resistant agent, the concentration of the prefabricated wear-resistant agent in ethanol is 400g / L, the ultrasonic frequency of the ultrasonic treatment is 95kHz, and the temperature is 45°C; the drying temperature is 105°C.

[0062] The antioxidant is antioxidant 1010.

[0063] The dispersant is zinc stearate.

[0064] The stabilizer adopts calcium zinc composite stabilizer.

[0065] The thickness of the BOPP printing film is 70 μm, wherein the thickness of the polypropylene base layer is 30 μm, and the thickness of the wear-resistant layer is 40 μm.

[0066] The method for preparing the antibacterial high wear-resistant BOPP printed film comprises the following steps:

[0067] Step 1, drying the polypropylene resin, silane coupling agent and antistatic agent respectively, adding them to an extruder and mixing them evenly, and melt-extrude them to obtain a matrix melt; the temperature of the melt extrusion is 240-250° C.;

[0068] Step 2, adding polypropylene resin, anti-wear agent, antioxidant, dispersant and stabilizer to the extruder, mixing evenly, and melt-extrude to obtain a wear-resistant melt; the temperature of the melt extrusion is 230-240°C;

[0069] Step 3, the base melt and the wear-resistant melt are extruded in the order of the die lip of the double-layer structure extruder to obtain a film, and then rapidly cooled to obtain a cast sheet;

[0070] Step 4, stretching the cast sheet longitudinally at a constant temperature, and then stretching it transversely at a constant temperature, and cooling it to obtain an antibacterial and highly wear-resistant BOPP film, wherein the preheating temperature of the longitudinal stretching is 145°C, the stretching temperature is 135°C, and the stretching ratio is 5 times; the preheating temperature of the transverse stretching is 170°C, the stretching temperature is 165°C, and the stretching ratio is 8 times, and the cooling is natural cooling and rapid cooling to fix the shape.

[0071] Comparative Example 1

[0072] The only difference between Comparative Example 1 and Example 3 is that the anti-wear agent is silicon dioxide particles, and the particle size of the silicon dioxide particles is about 5 μm.

[0073] Comparative Example 2

[0074] The only difference between Comparative Example 1 and Example 3 is that the anti-wear agent is a mixture of silicon dioxide particles and chitosan in a mass ratio of 3:1, and the particle size of the silicon dioxide particles is about 5 μm.

[0075] Performance Testing

[0076] The performance tests of the antibacterial wear-resistant BOPP printed films of Examples 1-3 and Comparative Examples 1-2 were performed, and the results were as follows:

[0077]

[0078] From the comparison of the above examples 1-3 and comparative examples 1-2, it can be concluded that the wear-resistant agent provided in the technical solution can effectively improve the wear resistance of the printed film, and also provide good antibacterial properties of the wear-resistant layer. The printed film prepared by this method has a slight decrease in mechanical strength, but the impact is not significant, and still has good mechanical properties.

[0079] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.

Claims

1. A method for preparing an antibacterial and highly wear-resistant BOPP printed film, characterized in that: The BOPP printing film comprises a polypropylene base layer and a wear-resistant layer coated on the surface of the polypropylene base layer, the thickness of the polypropylene base layer is 20-40 μm, the thickness of the wear-resistant layer is 30-50 μm, and the wear-resistant layer has an antibacterial effect; The mass ratio of the polypropylene base layer is: 70-80 parts of polypropylene resin, 3-6 parts of silane coupling agent, and 0.1-0.5 parts of antistatic agent; The mass ratio of the wear-resistant layer is: 50-70 parts of polypropylene resin, 30-50 parts of wear-resistant agent, 1-3 parts of antioxidant, 0.4-0.6 parts of dispersant, and 2-4 parts of stabilizer; The method for preparing the antibacterial high wear-resistant BOPP printed film comprises the following steps: Step 1, drying the polypropylene resin, silane coupling agent and antistatic agent respectively, adding them to an extruder and mixing them evenly, and melt-extrude them to obtain a matrix melt; the temperature of the melt extrusion is 240-250° C.; Step 2, adding polypropylene resin, anti-wear agent, antioxidant, dispersant and stabilizer to the extruder, mixing evenly, and melt-extrude to obtain a wear-resistant melt; the temperature of the melt extrusion is 230-240°C; Step 3, the base melt and the wear-resistant melt are extruded in the order of the die lip of the double-layer structure extruder to obtain a film, and then rapidly cooled to obtain a cast sheet; Step 4, the cast sheet is longitudinally stretched at a constant temperature, and then transversely stretched at a constant temperature, and then cooled to obtain an antibacterial and highly wear-resistant BOPP film, wherein the preheating temperature of the longitudinal stretching is 140-150°C, the stretching temperature is 130-140°C, and the stretching ratio is 4-6 times; the preheating temperature of the transverse stretching is 165-175°C, the stretching temperature is 160-170°C, and the stretching ratio is 7-9 times, and the cooling is natural cooling and rapid cooling to set the shape; The wear-resistant agent adopts a chitosan-silicon composite wear-resistant agent, wherein the chitosan-silicon composite wear-resistant agent has chitosan as the core and a silicon material as the porous protective shell, and there is a gap between the core and the porous protective shell; and the preparation method of the chitosan-silicon composite wear-resistant agent comprises the following steps: a1, dispersing chitosan in ethanol to form a suspension, then adding polyvinyl pyrrolidone and ultrasonically treating for 10-30 minutes, filtering and drying to obtain polyvinyl pyrrolidone-coated chitosan; the mass ratio of chitosan to ethanol is 1:5-7, the dispersion treatment is mechanically stirred at a stirring speed of 1000-2000 r / min, the mass ratio of polyvinyl pyrrolidone to chitosan is 1:2-3, the ultrasonic frequency of the ultrasonic treatment is 70-90 kHz, the ultrasonic temperature is 20-30°C; the drying temperature is 80-90°C; a2, adding trichlorophenylsilane and ethyl cellulose to ether and stirring evenly, then adding polyvinyl pyrrolidone to wrap chitosan and stirring for 10-20 minutes, filtering and drying to obtain coated chitosan, the mass ratio of trichlorophenylsilane to ethyl cellulose is 6-8:1, the concentration of ethyl cellulose in ether is 30-70g / L, the stirring speed for stirring evenly is 1000-2000r / min, the mass ratio of polyvinyl pyrrolidone-wrapped chitosan to trichlorophenylsilane is 1:1.2-1.5, the stirring speed is 100-200r / min, and the drying temperature is 40-50°C; a3, allowing the coated chitosan to stand for 1-2 hours and subjecting it to a temperature treatment for 0.5-1 hour to obtain a prefabricated anti-wear agent, wherein the atmosphere of the standing state is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8-10:1; and the temperature of the temperature treatment is 120-140°C; a4, put the prefabricated anti-wear agent into ethanol and ultrasonically treat it for 1-3h, filter it, wash it with ethanol and dry it to obtain the anti-wear agent, the concentration of the prefabricated anti-wear agent in ethanol is 200-500g / L, the ultrasonic frequency of the ultrasonic treatment is 90-100kHz, the temperature is 40-50℃; the drying temperature is 100-110℃.

2. The method for preparing the antibacterial high wear-resistant BOPP printed film according to claim 1, characterized in that: The polypropylene resin in the polypropylene base layer is homopolymerized polypropylene, and the antistatic agent is ethoxylated alkyl acid amine.

3. The method for preparing the antibacterial high wear-resistant BOPP printed film according to claim 1, characterized in that: The polypropylene resin in the wear-resistant layer is homopolymer polypropylene, with a brand name of F280F, produced in Shaoxing, with a melt index of 2.8 g / 10 min, and a melting condition of 230° C. and 2.16 kg.

4. The method for preparing the antibacterial high wear-resistant BOPP printed film according to claim 1, characterized in that: The antioxidant is antioxidant 1010 or antioxidant 168.

5. The method for preparing the antibacterial high wear-resistant BOPP printed film according to claim 1, characterized in that: The dispersant is zinc stearate.

6. The method for preparing the antibacterial high wear-resistant BOPP printed film according to claim 1, characterized in that: The stabilizer is a calcium-zinc composite stabilizer.

Citation Information

Patent Citations

  • Chitosan silicone-acrylate copolymer composite polrvinyl chloride antibacterial material and preparation method and application thereof

    CN102504108A

  • High-temperature resistant ceramic antibacterial agent coated with inorganic nano-material and preparation technology of high-temperature resistant ceramic antibacterial agent

    CN103193488A